Lockdown length and strength: Labour-market effects in Germany during the COVID-19 pandemic - Anja Bauer; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
This paper evaluates the short-term labour market impact of the COVID-19 containment measures in Germany. It examines two dimensions of the first lockdown in Germany, namely the length and the strength of the lockdown. While the assessment of the length is conducted via variation across regions and time in closing days and curfews, the latter uses the degree of closure in different sectors. For the length of the lockdown we find that an additional day of closure lead to an increase in the separation rate of 2.7 percent and a decrease in the jobfinding rate of 1.8 percent. For the strength of the lockdown the results show that a higher degree of closure increases separations and lower job findings to a similar extent. In both dimensions, we find that the effects are non-linear over time. Given this approach, we find that 31 percent of the considerably increased inflows from employment into unemployment, and 33 percent of the reduced outflows from unemployment to employment in the first wave were due to the treatment effect of the lockdown measures. In sum, the lockdown measures increased unemployment in the short run by 80,000 persons. – – Dieses Papier evaluiert die kurzfristigen Arbeitsmarkteffekte der COVID-19-Eindämmungsmaßnahmen in Deutschland. Wir untersuchen zwei verschiedene Dimensionen des ersten Lockdowns in Deutschland, nämlich die Länge und die Stärke des Lockdowns. Während die Länge über die regionale und zeitliche Variation der Schließungstage und Ausgangssperren erfolgt, wird für die Stärke der Grad der Schließung in verschiedenen Branchen herangezogen. Für die Länge des Lockdowns finden wir, dass ein zusätzlicher Tag zu einem Anstieg der Entlassungsrate um 2,7 Prozent und einem Rückgang der Einstellungsrate um 1,8 Prozent führt. Für die Stärke der Schließung zeigen die Ergebnisse, dass ein höherer Grad der Schließung die Entlassungen erhöht und die Einstellungen in ähnlichem Ausmaß senkt. In beiden Dimensionen stellen wir fest, dass die Effekte im Zeitverlauf nicht linear sind. Mit diesem Ansatz finden wir, dass 31 Prozent der deutlich erhöhten Zuflüsse aus Beschäftigung in Arbeitslosigkeit und 33 Prozent der verringerten Abflüsse aus Arbeitslosigkeit in Beschäftigung in der ersten Welle auf die Schließungsmaßnahmen zurückzuführen sind. In Summe erhöhten die Eindämmungsmaßnahmen die Arbeitslosigkeit in der kurzen Frist um 80.000 Personen.
Keywords: J6; E24; 330; containment measures; COVID-19; job finding rate; separation rate